Zeolite–cellulose composite membranes: Synthesis and applications in metals and bacteria removal. Issue 4 (August 2020) - Baghdad, Karima; Hasnaoui, Abdelkrim M.
Graphical abstract: Abstract: New zeolite composite membranes were synthesized using faujasite and cellulose membrane as precursor, two types of composites were prepared with different routes and characterized by Scanning electron microscopy, X-ray powder diffraction, Infrared spectroscopy, Raman and N2 sorption. The composites were investigated in water treatment via ion exchange and filtration processes. The removal rate of divalent ions (Ca 2+, Mg 2+, Pb 2+ and Cu 2+ ) exceeded 90 % for different parameters of concentrations and pH studied. The ability of faujasite-cellulose composite membranes was also verified in terms of water purification from bacteria (Total coliforms, Escherichia coli, Enterococci and Clostridium), the results revealed height removal values for less than 100 colonies per 100 mL.